2022
DOI: 10.1182/bloodadvances.2021006827
|View full text |Cite
|
Sign up to set email alerts
|

Reduced intensity hematopoietic stem cell transplantation for accelerated-phase myelofibrosis

Abstract: Accelerated-phase (AP) myelofibrosis, currently defined by circulating blasts 10-19%, usually confers very high risk for progression and poor outcome. The outcome of hematopoietic stem cell transplantation for AP myelofibrosis has not been evaluated yet. We analyzed the outcome of 349 clinically and genetically annotated patients with primary or secondary myelofibrosis undergoing reduced intensity transplantation, of whom 35 had AP myelofibrosis. In comparison with chronic-phase (CP, <10% blasts), media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 39 publications
3
19
0
Order By: Relevance
“…11,17,21 Interestingly, a recent study suggested that the number of blasts at time of all-HCT was not relevant in MPN-CP and MPN-AP patients undergoing allo-HCT. 35 In our analysis, however, pre transplant CR was a favorable prognostic factor for the endpoints of OS, PFS, RI and NRM. Of note, data regarding measurable residual disease (MRD) was unavailable in our study and in our opinion the role of MRD following BP-MPN allo-HCT requires systematic prospective evaluation.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…11,17,21 Interestingly, a recent study suggested that the number of blasts at time of all-HCT was not relevant in MPN-CP and MPN-AP patients undergoing allo-HCT. 35 In our analysis, however, pre transplant CR was a favorable prognostic factor for the endpoints of OS, PFS, RI and NRM. Of note, data regarding measurable residual disease (MRD) was unavailable in our study and in our opinion the role of MRD following BP-MPN allo-HCT requires systematic prospective evaluation.…”
Section: Discussionmentioning
confidence: 47%
“…The CIBMTR reported data on a cohort of 177 BP‐MPN patients undergoing allo‐HCT, highlighting that the number of blasts was not a prognostic factor for survival, 20 whereas in contrast, in other allo‐HCT retrospective studies there was a clear association regarding disease status at time of allo‐HCT and long‐term survival 11,17,21 . Interestingly, a recent study suggested that the number of blasts at time of all‐HCT was not relevant in MPN‐CP and MPN‐AP patients undergoing allo‐HCT 35 . In our analysis, however, pre transplant CR was a favorable prognostic factor for the endpoints of OS, PFS, RI and NRM.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Pre‐transplant bridging chemotherapy is currently not indicated in chronic phase MPN and its value in MPN‐AP is not certain; in a retrospective report of 35 patients with MPN‐AP and receiving reduced intensity AHSCT, 5‐year survival was 65% versus 64% in the comparator arm of patients with chronic phase disease, although relapse rate was higher in the former 148 . Increased post‐transplant relapse rate was also noted in MPN‐BP patients transplanted with active disease 149 .…”
Section: Blast Phase Myeloproliferative Neoplasmmentioning
confidence: 99%
“…Pre‐transplant bridging chemotherapy is currently not indicated in chronic phase MPN and its value in MPN‐AP is not certain; in a retrospective report of 35 patients with MPN‐AP and receiving reduced intensity ASCT, 5‐year survival was 65% versus 64% in the comparator arm of patients with chronic phase disease, although relapse rate was higher in the former 39 . Increased post‐transplant relapse rate was also noted in the current report by Orti et al in their patients with MPN‐BP transplanted with active disease 26 .…”
mentioning
confidence: 99%